A case of intracranial myxoid mesenchymal tumor with EWSR1:CREM fusion in an adult female: Extensive immunohistochemical evaluation. Issue 4 (13th July 2021) - Kambe, Atsushi; Kuwamoto, Satoshi; Shimizu, Tsuyoshi; Amisaki, Hidefumi; Sakamoto, Makoto; Inagaki, Hirotaka; Kurosaki, Masamichi
Abstract : Intracranial myxoid mesenchymal tumor (IMMT) is a recently described, extremely rare group of neoplasms characterized by fusions between the female‐expressed transcript (FET) family genes and the cAMP response element‐binding protein (CREB) family genes. Controversy persists regarding whether the tumor is a myxoid variant of angiomatoid fibrous histiocytoma or a completely distinct clinicopathological entity. Here, we report a case of IMMT arising in the posterior fossa in a 65‐year‐old woman with a history of breast cancer. We performed total removal of the tumor, which histologically demonstrated features characteristic of IMMT but also bore a partial resemblance to conventional angiomatoid fibrous histiocytoma. Immunohistochemically, tumor cells were diffusely positive for desmin, vimentin, cluster of differentiation (CD) 99 (CD99), glucose transporter‐1, and cytokeratin (CK) 8/18 (CK8/18), and focally positive for CK7, epithelial membrane antigen, mucin 4, anaplastic lymphoma kinase, calponin, and CD68. Molecular genetic analysis revealed a fusion between the Ewing sarcoma breakpoint region 1 (EWSR1) gene ( EWSR1 ) and the cAMP‐responsive element modulator (CREM) gene ( CREM ) called EWSR1:CREM fusion, which confirmed the diagnosis. The overlap of the pathological features of IMMTs and angiomatoid fibrous histiocytomas may support the recent theory that these tumors are two manifestations of a single entity. Moreover, our study indicated the broad spectrum of immunohistochemical phenotypes of these tumors, which should be noted during diagnosis. Further studies are needed to elucidate the histopathological concept, long‐term prognosis, optimal treatment strategy, and factors associated with the prognosis and therapeutic options of this condition.